2015
DOI: 10.1186/s12905-015-0257-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of intimate partner violence against women during a time of rapid social transition in Rwanda: analysis of the 2005 and 2010 demographic and health surveys

Abstract: BackgroundIn Rwanda, women who self-reported in household surveys ever experiencing intimate partner violence (IPV) increased from 34 % in 2005 to 56 % in 2010. This coincided with a new constitution and majority-female elected parliament in 2003, and 2008 legislation protecting against gender-based violence. The increase in self-reported IPV may reflect improved social power for women, and/or disruptions to traditional gender roles that increased actual IPV.MethodsThis is a cross-sectional study of IPV in 433… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 33 publications
9
46
0
Order By: Relevance
“…Theoretical and statistical approaches should be complex enough to reflect these intersections. Recent studies conducted in the United States (Katerndahl et al, 2014; Miller-Graff & Graham-Bermann, 2014) and Africa (Thomson et al, 2015) have begun examining multidirectional influences on IPV, supporting the associations seen between indicators of poverty, alcohol use, relational dynamics, and GBV.…”
Section: Discussionmentioning
confidence: 87%
“…Theoretical and statistical approaches should be complex enough to reflect these intersections. Recent studies conducted in the United States (Katerndahl et al, 2014; Miller-Graff & Graham-Bermann, 2014) and Africa (Thomson et al, 2015) have begun examining multidirectional influences on IPV, supporting the associations seen between indicators of poverty, alcohol use, relational dynamics, and GBV.…”
Section: Discussionmentioning
confidence: 87%
“…An analysis by the WHO (World Health Organization) [18] combining data from 77 studies in 56 countries estimated that in Africa, 37% of women have already been a physical or sexual victim of violence by an Intimate Partner. These data were like the eastern Mediterranean (37%) and the Southeast of Asia (38%), and higher than in the Americas (30%), Europe (25%) and West Pacific (25%) [19].…”
Section: Discussionmentioning
confidence: 65%
“…The known associated factors responsible for high rate of domestic violence are age, education, employment, wealth status among others(19,31). The result of this study revealed that domestic violence was very evident among ever-married women of ages 15-19, 20-24, 25-29 and 30-34 years in Nigeria, Kenya and Mozambique.…”
Section: Discussionmentioning
confidence: 99%
“…The length of time between marriage date and the date of first domestic violence was used as the dependent variable in this study while age, education, employment, residence and wealth indicators were used as independent variable. They have been identified in prior studies as contributing factors to domestic violence among women(4,10,12,19).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation